2018
DOI: 10.1097/pcc.0000000000001681
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Development of Postoperative Delirium in Pediatric Intensive Care Patients

Abstract: A high prevalence of delirium was noted in the PICU, and several perioperative risk factors were identified. Our data may be a base for development of strategies to prevent and treat postoperative delirium in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 30 publications
2
38
2
Order By: Relevance
“…However, in the context of postoperative delirium in the PICU, we could recently show that fentanyl increases the risk for delirium in a dose-dependent way and that this could probably be attributed to substance-specific anticholinergic effects. 21 Therefore, it would be very interesting to see the results of the 322 patients from the three unpublished registered trials (NCT02753725, 22 NCT03010540, 23 NCT03062488) 24 on intraoperative fentanyl given at different doses.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the context of postoperative delirium in the PICU, we could recently show that fentanyl increases the risk for delirium in a dose-dependent way and that this could probably be attributed to substance-specific anticholinergic effects. 21 Therefore, it would be very interesting to see the results of the 322 patients from the three unpublished registered trials (NCT02753725, 22 NCT03010540, 23 NCT03062488) 24 on intraoperative fentanyl given at different doses.…”
Section: Discussionmentioning
confidence: 99%
“…Minimizing pain with intraoperative Fentanyl given at a mean dose of 2.5 µg/kg at the end of surgery reduced the incidence of ED in a study by Cohen et al 13 . However, in the context of postoperative delirium in the PICU we could recently show that fentanyl increases the risk for delirium in a dose-dependent way and that this could probably attributed to substance-specific anticholinergic effects 14 . Therefore it would be very interesting to see the results of the 322 patients from the three unpublished registered trials (NCT02753725, NCT03010540, NCT03062488) on intraoperative fentanyl given at different doses.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] Another single-center prospective cohort study found that nearly 66% children were delirious after major surgery in pediatric intensive care unit (PICU). [ 19 ] This may be explained by following aspects. First, we focused on all children after major elective surgery rather than critically-ill children in PICU.…”
Section: Discussionmentioning
confidence: 99%
“…Putative risk factors for delirium development were extrapolated from a review of the pediatric and adult literature in medical and surgical patients. [ 19 ] Preoperative data collected included: sleep duration, fluid fasting time, severity of parental anxiety using Hamilton Anxiety Scale. [ 20 ] Intraoperative data collected included: length of anesthesia, length of surgery, and blood loss.…”
Section: Methodsmentioning
confidence: 99%